Prevelance of hepatitis D co-enfection in children with hepatitis B infection: Cross-sectional analyses from Western Turkey - Funda ÖZGENÇ; Çiğdem ÖMÜR ECEVİT and Gülin ERDEMİR and Rüçhan SERTÖZ and Raşit Vural YAĞCI (Turkish Journal of Gastroenterology, 2019)
-